Evaluation of aminopyrrolidine amide to improve chloride transport in CFTR-defective cells. (15th September 2022) - Huguet, Florentin; Guellec, Julie; Kerbiriou, Mathieu; Gandy, Maxime; Thomas, Johan; Férec, Claude; Benz, Nathalie; Trouvé, Pascal
Graphical abstract: Abstract: The aminopyrrolidine amide PF-429242 is a specific inhibitor of the Site-1 Protease which is responsible for the cleavage, and thus the activation of the Activating Transcription Factor 6 that down regulates many genes, during the Unfolded Protein Response. We hypothesized that PF-429242 could be used to prevent the ATF6-dependent down regulation of some genes. We chose the CFTR gene encoding the CFTR chloride channel as a model because it is down-regulated by ATF6 in Cystic Fibrosis. We evaluated the action of PF-429242 in human bronchial cells expressing the most frequent mutation of CFTR (p.Phe508del) found in patients. We observed that PF-429242 increases the synthesis of the mRNA and the protein encoded by the CFTR gene harbouring the mutation. We also observed that PF-429242 alleviates the defects of the p.Phe508del-CFTR channel in human Cystic Fibrosis cells. Our results suggest that aminopyrrolidine amide is a potential therapeutic target for Cystic Fibrosis that could also have beneficial effects in other diseases involving CFTR, such as the Chronic Obstructive Pulmonary Disease.